From Consumers to Co-creators: The Role of Social Media in Shaping Participatory Christian Learning Among Millennials and Gen Z - Majesty, Gilbert Timothy; Sianturi, Juliana; Pane, Litos Sitorus; Jura, Demsy (PT FORMOSA CENDEKIA GLOBAL, 2025)
This qualitative study, grounded in a constructivist framework, investigates the role of social media in transforming Millennials and Gen Z from passive consumers into active co-creators of Christian learning. Through an analysis of participatory interactions on platforms like Instagram and TikTok, the research examines how these digital environments facilitate the collective construction of religious knowledge. Findings reveal that user-generated content, dialogical exchanges, and communal interpretation of scripture empower young believers to shape personalized and contextually relevant theological understandings. The study concludes that social media acts as a pivotal catalyst for a participatory paradigm shift, fostering a dynamic, peer-driven faith formation process that redefines contemporary Christian pedagogy.